Echography. More than a complementary method in the diagnosis of canine heartworm disease. Case report - Baiza-Molina, David (2023)
Heartworm disease is a parasitic infection with worldwide distribution, caused by the Dirofilaria immitis nematode and transmitted by culicid mosquitoes, with canines being the main hosts. Serologic tests provide some diagnostic help but are not conclusive. This report describes a clinical case of a canine in which the serological tests for filarial detection and the tests for the detection of microfilaraemia were inconclusive. However, the use of standardized protocols using ultrasound as part of the physical examination, evidenced the presence of cardiac filarials. The importance of reporting this case is to present a clinical protocol that includes cardiac ultrasound for an accurate diagnostic approach.